Pengaruh Metode Bercerita Menggunakan Audio Untuk Meningkatkan Nilai Moral Anak Usia 5-6 Tahun - Megawati; Muhammad Yusri Bachtiar; Fadhilah Afifah (Jurnal Kajian Anak (J-Sanak), 2025)
This study shows the low understanding of moral values ​​by looking at technological advances that can help early childhood moral learning by using audio stories as a more interesting learning tool. This study aims to determine the Effect of Storytelling Methods Using Audio to Improve Moral Values ​​of Children Aged 5-6 Years in Kindergarten Aisyiyah Bustanul Athfal (ABA) III. The approach used is a quantitative approach with a Quasi Experimental Design research type using a Nonequivalent Control Group Design. The population in this study were all group B children aged 5-6 years in Kindergarten Aisyiyah Bustanul Athfal (ABA) III, with a total of 20 children consisting of 10 children in class B1 as the experimental group and 10 children in class B2 as the control group. The sampling technique was saturated sampling. Data collection techniques were carried out through observation, tests, and documentation. The data were analyzed with descriptive statistics and non-parametric statistics using the Wilcoxon Sign Rank Test in SPSS version 24. The results of the study showed that the use of storytelling methods using audio can improve children's moral values, this is evidenced by a significant increase in k in the experimental group with a significance value of 0.005 <0.05, while the control group showed a significance value of 0.257> 0.05. Thus, it can be concluded that the storytelling method using audio has a significant effect on improving the moral values ​​of children aged 5-6 years at Aisyiyah Bustanul Athfal (ABA) III Kindergarten